Effect of the autoimmune-associated genetic variant PTPN22 R620W on neutrophil activation and function in patients with insulin-dependent diabetes mellitus - Belcastro, Eugenia; Cudini, Annamaria; Mezzani, Irene; Petrini, Stefania; D’Oria, Valentina; Schiaffini, Riccardo; Scarsella, Marco; Russo, Anna Lo; Fierabracci, Alessandra (Frontiers in Immunology, 2025)
IntroductionRecent evidence highlights neutrophils’ role in initiating/sustaining aberrant immune responses in type 1 diabetes (T1D). The PTPN22 C1858T variant, a risk factor for several autoimmune conditions including T1D, affects T/B-cell receptor signaling. This study investigates its contribution to the altered neutrophil activation and function in T1D.Materials and methodsNeutrophils were isolated from peripheral blood mononuclear cells (PBMCs) of wild-type (WT) C1858C, heterozygous (HET) C1858T T1D patients, and healthy controls (HD). Reactive oxygen species (ROS) levels were assessed using a fluorogenic probe by Fluorescence- Activated Cell Sorting (FACS) in tumor necrosis factor-alpha (TNF-α) primed, unprimed-N-formylmethionyl-leucyl-phenylalanine (fMLP) stimulated, and primed-stimulated neutrophils. Neutrophil adhesion/transmigration was evaluated via brightfield and epifluorescence microscopy on human umbilical vein endothelial cells (HUVECs).ResultsNeutrophil counts were increased in the female patients than in HD. ROS production was enhanced in the neutrophils of the HET patients versus WT controls under the different culture conditions. Furthermore, ROS levels were increased in the HET (n = 10) versus WT (n = 6) patients (p < 0.05). Neutrophil adhesion to HUVECs and transmigration through the monolayer were increased in the HET (n = 4) versus WT (n = 6) patients under both basal and TNF-α conditions (p < 0.0001).ConclusionNeutrophils from C1858T patients are more intrinsically active with increased ROS production and HUVEC adhesion/transmigration, suggesting enhanced contribution to the migration of other immunotypes from vessels into the pancreatic islets during T1D etiopathogenesis.